2005
DOI: 10.1158/1535-7163.mct-04-0280
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor (EGFR)–related protein inhibits multiple members of the EGFR family in colon and breast cancer cells

Abstract: Inactivation of epidermal growth factor receptor (EGFR) family members represents a promising strategy for the development of selective therapies against epithelial cancers. Current anti-EGFR therapies, such as cetuximab (Erbitux), gefitinib (Iressa), or trastuzumab (Herceptin), target EGFR or HER-2 but not both. Because solid tumors express different EGFRs, identification of inhibitor(s) targeting multiple EGFR family members may provide a therapeutic benefit to a broader patient population. We have identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…Major restriction of this study is that NIH/3T3 is a mouse broblast cell model and the genetic background may not be correlated with epithelia, though NIH/3T3 has been recognized as a cell line for tumorigenesis study in vitro and in vivo 17 . We could not observe EGFR expression in NIH/3T3 which is similar to previous studies showing that NIH/3T3 is lack of EGFR 55,56 . Therefore, we tried to use a normal colon cell, CCD-841CoN as a model and found that acrolein indeed induce activation of RAS/MAPK pathway which was similar to NIH/3T3 (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Major restriction of this study is that NIH/3T3 is a mouse broblast cell model and the genetic background may not be correlated with epithelia, though NIH/3T3 has been recognized as a cell line for tumorigenesis study in vitro and in vivo 17 . We could not observe EGFR expression in NIH/3T3 which is similar to previous studies showing that NIH/3T3 is lack of EGFR 55,56 . Therefore, we tried to use a normal colon cell, CCD-841CoN as a model and found that acrolein indeed induce activation of RAS/MAPK pathway which was similar to NIH/3T3 (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The major restriction of this study is that NIH/3T3 is a mouse fibroblast cell model, and the genetic background may not be correlated with epithelia, although NIH/3T3 has been recognized as a cell line for tumorigenesis studies in vitro and in vivo 17 , 55 , 56 . We could not observe EGFR expression in NIH/3T3 cells, which is similar to previous studies showing that NIH/3T3 cells lack EGFR 57 , 58 . Therefore, we tried to use a normal colon cell line, CCD-841CoN, as a model and found that acrolein indeed induced activation of the RAS/MAPK pathway, which was similar to NIH/3T3 (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…HT-29, a human colorectal cancer cell line with strong HER2 expression (Fig. 2 b) [ 22 , 23 ], was used in this study. Micelles labeled with iFluor 594 were used for the cell uptake assay.…”
Section: Resultsmentioning
confidence: 99%
“…Next, trastuzumab, a human anti-HER2 antibody, was conjugated to the micelle surface through EDS/NHS chemistry to generate trastuzumab-conjugated targeted micellar phthalocyanine (T-MP). T-MP would enable targeting to HER2 expressed on the surface of tumor cells, such as HT-29 colorectal cancer cells [ 22 , 23 ]. An orthotopic HT-29 colorectal tumor model was established [ 24 ], and metastasis to the mesenteric sentinel LN was observed.…”
Section: Introductionmentioning
confidence: 99%